The potential of cassava peel as acoustic panel material: A sustainable innovation in green engineering - Pramesti, Sharfina Djati; Aryani, Silfia Mona (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Natural waste is one of the materials that has the potential to become acoustic material because it has a porous texture and meets the requirements of suitable sound-absorbing materials. Utilizing natural waste as acoustic material can reduce cassava peel waste, especially in cassava peel processing industries, both from factories and home industries. Methods: This research is conducted to determine the potential of cassava peel waste as a natural material that can be utilized to create acoustic materials made from natural substances. In this study, cassava peel waste was tested as a sound-absorbing acoustic material using the impedance tube method. The sample was made by mixing finely ground cassava peel waste and PVAc (Poly-vinyl-acetate) white glue, then molding the mixture into circular molds with a diameter of 10 cm and thicknesses of 3.5 cm and 4 cm, respectively. Findings: The results indicate that the sample with a thickness of 3.5 cm has an absorption coefficient of 0.45 at a frequency of 500 Hz, while the 4 cm thick sample has an absorption coefficient of 0.32 at 600 Hz. Both samples show that cassava peel waste is a viable soundproofing material with absorption coefficients above 0.3, making it an effective, eco-friendly acoustic panel material. Conclusion: Cassava peel waste demonstrates good potential as an acoustic material, with promising sound absorption properties, making it an environmentally friendly and accessible alternative to conventional soundproofing materials. Novelty/Originality of this Study: This study introduces cassava peel waste as a sustainable and accessible material for acoustic applications, offering an innovative solution to both waste reduction and soundproofing. The research highlights the potential of using locally available natural waste, specifically cassava peel, in the creation of eco-friendly acoustic panels, which is a novel approach not widely explored in the acoustic material industry.